Entre a petição inicial e a sentença: trabalho pedagógico nos professores no projeto pedagógico do curso de Direito das instituições públicas gaúchas - Papalia, Franceli Bianquin Grigoletto (2020)
The research is part of Research Line 02 of the Graduate Program in Education, “Educational Public Policies, educational practices and their interfaces”, and was developed within the scope of Kairós - Study and Research Group on Work, Education and Educational Policies . To develop the present research, bibliographic and documentary researches were carried out, which sought to analyze how the pedagogical work of teachers is described, in the pedagogical projects of the Law Courses of public Higher Education Institutions in the State of Rio Grande do Sul. reference to Resolution no. 05/2018, from the Ministry of Education, which restructures all Law Courses nationwide. In addition, an analysis of the pedagogical projects of the Law Courses of public Higher Education Institutions was carried out, specifically, regarding the main categories of this research: “pedagogical work” and “Course of Law”. In this perspective, the research is based on the principles of dialectical analysis, and the data produced in the bibliographic research were analyzed and systematized, using bibliographic analysis as a reference. The structure of this dissertation was organized in a metaphorical way, having as reference the rite of a judicial process, delimiting all the main phases, which are, initial, instructive, final allegations (sanitation) and sentence. It was sought as a problematization, how is the pedagogical work of teachers from the Law course of public HEIs in Rio Grande do Sul described in the pedagogical projects? As main objective, it was elaborated: to analyze the evidences of the pedagogical work category in the pedagogical projects in the Law Courses of the Public Higher Education Institutions of Rio Grande do Sul, in face of the changes determined by the MEC Resolution 05/2018. The specific objectives foresee: to know the pedagogical projects in the Law Courses of the Public Higher Education Institutions in Rio Grande do Sul, in order to know which ones are adequate to the MEC Resolution 05/2018; carry out documentary study in the pedagogical projects in the Law Courses of public Higher Education Institutions in Rio Grande do Sul, regarding the pedagogical work category; to analyze the main changes and innovations that the MEC Resolution 05/2018 establishes for the Law Course of Public Higher Education Institutions in Rio Grande do Sul, regarding the category of pedagogical work for teachers. The analysis of pedagogical projects demonstrates the search for courses that demystifies the culture of the teacher who transmits knowledge. Finally, it is highlighted that the description of the teacher's pedagogical work is included in these documents.